The process of explanation - Krull, Douglas S.; Anderson, Craig A. (1997)
Presents a general model of the explanation process. The explanation process is initiated when an event occurs. Before an event can be explained, however, it must first be noticed. After perceivers notice an event, they must decide what it is that they have noticed. This interpretation is influenced by the perceiver's expectations. After interpreting an event, the person generates an initial explanation. After an initial explanation is generated, constraints play a significant role. If sufficient time and cognitive resources are available, a more effortful problem-based process begins. Problem-based explanations involve problem formulation and problem resolution. Next, the explainer must decide whether the best explanation produced in the problem resolution stage is satisfactory. Eventually, either the explainer arrives at a satisfactory explanation or the cognitive or motivational constraints cause the cycling to stop.